Circular and athermal atmospheric CO 2 capture by food waste-derived amyloid sorbents - Zhou Dong; Ming Dai; Felix Donat; Dominik Richert; Bin Dai; Paweł P. Ziemiański; Jiangtao Zhou; Milad Radiom; Mohammad Peydayesh; Yanwen Li; Xiuhuai Li; Hui Wu; et al. (Proceedings of the National Academy of Sciences, 2026)
Food waste contributes substantially to global CO 2 emissions, yet it also offers underutilized opportunities for climate change mitigation within and beyond the food system. Direct air capture technologies can help offset these emissions, but most current sorbents are synthetic, energy-intensive, and poorly aligned with circular-economy principles, while bio-based alternatives typically feature low CO 2 capacity and poor stability. Here, we upcycle proteins recovered from dairy and tofu waste streams into functional amyloid fibril microbeads for ambient CO 2 capture. Atomic-level design and templated molding enable lysine and glutamine residues within the fibrils, along with hydroxyl groups introduced by mild KOH treatment, to form abundant active sites for CO 2 capture, achieving up to 2.20 mmol g −1 under ambient air, and 2.51 mmol g −1 under simulated air (oxygen-free). The microbeads are regenerated within 10 to 12 min via alternating dilute acid–alkali mist without any thermal input and remain stable over 30 cycles. Life cycle assessment, ranking efficiency product, and techno-economic analysis reveal superior sustainability and cost efficiency compared with conventional sorbents, validating a circular economy approach that upcycles food waste into CO 2 sorbents, which can, if needed, ultimately be reintegrated into the food system.